2020
DOI: 10.37698/ashrej.v2i1.18
|View full text |Cite
|
Sign up to set email alerts
|

The Ecolinguistics of Malay Langkat Mantra

Abstract: This paper deals with the description of ecolinguistics on Malay Langkat mantra. The main objective of this paper is to explore especially the Malay Langkat mantra (especially those related to traditional medications) on the basis of the ecolinguistic study. Malay Langkat mantra was very popular amongst the Malay Langkat society in the past. The mantra was used by traditional medicine man called pawang/bomoh/dukun. He commonly has supernatural ability in medicating the local society in almost all kinds of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This research focuses on natural elements explored through an ecological approach that emphasizes the interconnectedness of phenomena and critical interdependence in the ecosystem where organisms live (Farhaeni, 2023). From a systemic perspective, the basis of an ecological outlook, objects are fundamentally networks embedded in a broader context (Natsir et al, 2020) The object of eco-critical study is evident in the nature-nurture-culture paradigm (Insani & Rokhim, 2021). It represents an ecological network connecting nature, preservation, and culture within the ecosphere (Setiawan et al, 2018).…”
Section: Symbolization Of Ecological Elements In Melawi Malay Medicin...mentioning
confidence: 99%
“…This research focuses on natural elements explored through an ecological approach that emphasizes the interconnectedness of phenomena and critical interdependence in the ecosystem where organisms live (Farhaeni, 2023). From a systemic perspective, the basis of an ecological outlook, objects are fundamentally networks embedded in a broader context (Natsir et al, 2020) The object of eco-critical study is evident in the nature-nurture-culture paradigm (Insani & Rokhim, 2021). It represents an ecological network connecting nature, preservation, and culture within the ecosphere (Setiawan et al, 2018).…”
Section: Symbolization Of Ecological Elements In Melawi Malay Medicin...mentioning
confidence: 99%
“…The application of nature's elements provides a powerful assurance and is one of the conditions that have to exist in the shaman or someone related to him in determining the effectiveness of the mantra. In their findings, Natsir et al (2020) suggested that the word mantra in Arabic referred to rukyah which means protection. Therefore, a mantra is carried out to ask for protection against evil.…”
Section: Literature Reviewmentioning
confidence: 99%